Biometric technology : authentication, biocryptography, and cloud-based architecture - Das, Ravindra. 4 0 16; 5 (Boca Raton : CRC Press/Taylor & Francis, 2015)
Preface Biometric technology has been around for a long time. For the most part, it has been accepted worldwide, without hesitation. It is a technology full of intrigue, mystique, awe, and misconceptions. Compared with other security technologies, biometrics receives the most scrutiny. Why is this so? It is this way because it is a piece of us, whether biological or physical, which is being examined in close detail. Most populations are accepting of this fact, but some are not, especially in the United States. In our society, we view biometrics as a violation of our privacy rights and civil liberties. However, truth be told, there are no magical powers behind biometrics. There are no black-box powers behind it either. It is just like any other security technology, with its fair share of benefits as well as flaws. Just like a computer program, it is literally garbage in-garbage out. It is the goal of this book to dispel the myths and disbeliefs about biometrics as well as to review the strong benefits it has to offer to society, populations, and corporations. In addition, biometrics has a great future ahead of it in terms of research and development, which this book also reviews, by way of cryptography and cloud applications. Although this book can be easily read and understood by just about anybody, it is primarily geared toward the corporate-level executive who is considering implementing biometric technology at their business or organization--
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Biometric identification. -- 20; 20; 2